The influence of self-compacting steel fibre reinforced concrete infill on the flexure strength and ductility of masonry walls - Oliveira, Luiz António Pereira de (2010)
This paper presents an experimental study on the influence of longitudinal reinforcement ratio and steel fibre volume in self-compacting concrete infill on the strength and ductility of reinforced masonry walls subjected to flexure. Flexure tests were performed as four-point bending tests on twelve walls. The analysis of the concrete infill contribution to the walls capacity is made considering recent recommendations for steel fibre reinforced concrete design. A ductility index was defined and applied to study the ductility behaviour of the masonry walls. The analysed variables are the longitudinal reinforcement ratio and the steel fibre volume in the concrete infill.